Diagnosis of Allergic and Nonallergic Food Intolerance in Children - A. A. Cheburkin (Вопросы современной педиатрии, 2013)
Because the incorrect food avoidance affects quality of life and nutrition, especially in children, there is possible harm in over-diagnosing food allergy. The approach to the proper diagnosis of food allergy and nonallergic intolerance requires consideration of the medical history, tests for food-specific IgE antibodies, skin puncture tests. Pediatrist must appreciate that a positive test for food-specific IgE or skin puncture test primarily denotes sensitization and may not confirm clinical allergy. Food elimination diet or oral food challenge is required for diagnosis confirmation. Additional procedures may be needed, depending on the differential diagnosis of IgE mediated or non-IgE mediated food intolerance.